The Impact of Using Idioms Card Game Media “FARMIDIOMS” in Language Art Subject to Increase Literacy in Elementary Students - Putri, Agusta Gracia Wahyu Harmoko; Juneau, Janelle L. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The literacy problem among elementary students persists as a significant challenge in the Indonesian education system. Literacy is one of the main focuses in elementary education. In order to increase literacy skills in students, teaching aids is an good option that can be applied in the teaching learning process. This research developed card game media called FARMIDIOMS for idioms topic in Language Arts for 3rd grade students to increase student literacy skills at Tritunggal Christian Elementary School-Semarang, Indonesia. This research and development method uses the Four-D model by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel created in 1974. There are 4 main stages, namely Define, Design, Develop, and Disseminate. This research was carried until the Develop stage due to limited time. The material expert validation test results obtained an actual score of 70 from the ideal score 75 which represents 93% and is in the “Very High” category. The media expert validation test results obtained an actual score of 66 from the ideal score of 70 which represents 94% and is in the “Very High” category. The results of the teacher and student response questionnaire also showed results in the "Very High" category. The students’ results in pre-test and post-test showed a significant increase with the Paired Samples T Test result Sig. (2-tailed) gets a result of 0.001 smaller than 0.05. From this data it can be concluded that the usage of the card game FARMIDIOMS are valid, practical, and effective in increaseing literacy skills in 3rd grade students.